Le contenu iconographique du journal Le Devoir de 1945 à 2005 - Jean de Bonville; Sylvie Demers (Communication)
This article offers a historical overview of the pictorial contents of the Montreal newspaper Le Devoir, from 1945 to 2005. Based on content analysis, this research highlights the changes in the two major roles more or less implicitly assigned to photography: reporting events and making the newspaper more attractive. The authors examine the defining nature of published pictures and their allotted space in the paper through the decades.